Sensitivity Analysis on Predicted Microwave Performance of Mode Converters with Geometrical Tolerances for 42-GHz Transmission Line Components. (3rd April 2019) - Sathyanarayana, K.; Kulkarni, S. V.; Patel, Amit; Bhatt, Pujita; Vala, Alpesh; Mewada, Hiren; Mahant, Keyur
Abstract: The impact of geometric tolerances of the mode converters on the microwave performance of the respective mode converters is studied. It is used as a guiding principle for stipulating the fabrication tolerances on various high-power microwave components. To carry out the simulation studies, Microwave Studio- Computer Simulation Technology software has been used. All the mode converters and transmission line components have been designed and benchmarked using simulation studies. The TE-03 to TE-02 (TE-mn where m and n are radial and azimuthal variation of fields) mode converter is taken as an example. The predicted microwave performance with estimated geometric tolerances is elucidated. Details of the same are available in the various microwave performance plots. Similar simulation studies have been carried out on the other mode converters. The results of the same are highlighted and summarized. Further, the microwave performance of these high-power components with respect to the fabrication tolerances on the internal diameter is also explored and highlighted. It has been found that by and large the cumulative mechanical tolerances on the total length, structural profile inside the mode converter, radius of the mode converter, and other mechanical dimensions are stringent. Based on the simulation studies, cumulative mechanical tolerances beyond approximately ±100 µm during fabrication are not preferred. The aim to obtain the finished product based on the guidelines from simulation studies has been the main theme of the exercise.